Testing the Intention of Employees in Local Government to Adopt Blockchain Technology in Accounting Information Systems (AIS) (Public Accounting and Sustainability, 2024)
Research aims: This study aims to determine the intention of local government employees to adopt blockchain technology in Accounting Information Systems (AIS) using the Technology Readiness and Acceptance Model (TRAM) theory. Design/Methodology/Approach: The research participants were individuals employed in Local Government Units (LGUs)  in Yogyakarta Special Region Province who were selected through a purposive sampling technique. Data were collected using a questionnaire and analyzed utilizing the Partial Least Square method. Research findings: The results revealed that the perceived usefulness of blockchain technology in AIS was determined by comfort, optimism, and security from fraud. Meanwhile, the perceived ease of use was determined by comfort, innovation, and security from fraud. These results also found that perceived usefulness and perceived ease of use positively influenced the intention of local government employees to use blockchain technology in AIS. Theoretical contribution/Originality: This research contributes to validating the TRAM theory in the context of blockchain technology adoption in AIS in local governments. Practitioner/Policy implication: The research findings offer valuable insight for relevant authorities, namely the Indonesian Ministry of Home Affairs, Ministry of Communication and Information, and local government entities, to prepare for implementing blockchain technology in AIS in local government. Research limitation/Implication: The study was conducted using quantitative methods with a limited sample size.